Marine Resource Recovery Following the COVID-19 Event in Southern Thailand - Sirirat Somchuea; Mullica Jaroensutasinee; Krisanadej Jaroensutasinee (Salehan Institute of Higher Education, 2022)
This study investigated coral and reef fish recovery following the COVID-19 event between low and high environmental disturbance reefs at Racha Yai Island, Southern Thailand. Three and four 50-m permanent line transects were set at low and high environmental reefs to collect the percent of live coral cover, fish diversity and abundance, and fish trophic-functional groups based on diet and habitat use. Our results showed a significant rise in the percentage of live coral cover, the number of individual fish, the number of fish species, and species richness at both bays following the COVID-19 lockdown due to a crucial reduction in human activities on the reef. In addition, there were increases in the number of corallivore fishes belonging to Chaetodontidae and Pomacentridae families and a reduction of omnivorous fish at the fish-feeding tourist attraction reefs due during the COVID-19 lockdown due to reducing fish-feeding tourism. This indicated that restricted human activities and reduced anthropogenic stress on a coral reef may have substantial short-term impacts on reef fish diversity. Our insights could help designate guidelines to manage tourist impacts on coral reefs and aid in their prolonged persistence. Doi: 10.28991/CEJ-2022-08-11-011 Full Text: PDF